2020
DOI: 10.1177/1362361320942092
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions and concerns about physical activity participation among adolescents with autism spectrum disorder

Abstract: The parents of adolescents with autism spectrum disorder have a vital and proactive role in encouraging healthy physical activity habits, and they possess important knowledge about the adolescents’ needs when it comes to enhancing participation in physical activity. But promoting healthy physical activity habits in adolescents can be difficult. The purpose of this study was thus to describe parents’ perceptions of their adolescent child’s participation in physical activity and to describe the parental role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
1
8
0
Order By: Relevance
“…These findings suggest that nurses weigh the tradeoffs between benefits and barriers when suggesting physical activity to people with ASD. These findings are consistent with research from Arnell et al (2020) where parents of teens with ASD noted the many benefits of physical activity but found that promoting such behaviors was “an overwhelming task,” given personal and social barriers in place. Thus, it is important for researchers and policy makers to take into account both benefits and barriers, as well as their interaction, when considering physical activity promotion.…”
Section: Discussionsupporting
confidence: 88%
“…These findings suggest that nurses weigh the tradeoffs between benefits and barriers when suggesting physical activity to people with ASD. These findings are consistent with research from Arnell et al (2020) where parents of teens with ASD noted the many benefits of physical activity but found that promoting such behaviors was “an overwhelming task,” given personal and social barriers in place. Thus, it is important for researchers and policy makers to take into account both benefits and barriers, as well as their interaction, when considering physical activity promotion.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the aforementioned first group of studies, we included the ones revised that studied the relationship between physical activity and emotional well-being in the general population (e.g., [ 87 ]) and in ASD participants (e.g., [ 88 ]). In general terms, they found that the effects of confinement have led to a decrease in physical activities in ASD participants and caused an increase in the amount screens hours exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may be compounded among children with ASD due to their unique social and communication behaviors associated with ASD (Corvey et al, 2016). This speculation is supported by research in which children with ASD and their parents reported a host of social barriers to PA, including stress that arise from social interaction (Arnell et al, 2020), being victims of bullying in PA settings, being excluded from activities by peers or practitioners (e.g. physical education teachers) (Blagrave & Colombo-Dougovito, 2019;Healy et al, 2013;Must et al, 2015), and having difficulty initiating social interactions (Obrusnikova & Miccinello, 2012).…”
Section: Discussionmentioning
confidence: 98%